MENGENAL TANAMAN OBAT DI LINGKUNGAN PEKARANGAN DAN CARA PENGGUNAANNYA - Is Zunaini Nursinah (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2008)
Changes in lifestyle have resulted in changes in disease patterns. While the purpose of health development is to enhance society's ability to live healthy and able to overcome the simple health problems, especially prevention and health improvement. Changing lifestyle into a healthy diet is one way for the bocfy to be healthy. To support health as well take advantage of garden plants which is the ancestral heritage needs to be developed and introduced in the community. Medicinal plants of family an advanced means of supply of drugs or herbal medicine that is by planting crops on the environment home and family at a time can be used for health.